INSTRUMENTAL EXAMINATION METHODS IN ASSESSING THE IMMEDIATE RESULTS OF CORRECTION OF ABNORMAL PULMONARY VEIN DRAINAGE - Mamatov M. A.; Abrolov H. K.; Ikramova F. D. (Web of Journals Publishing, 2024)
In this article, the clinical material consisted of 221 patients with various types of ADPV. The age of the operated patients ranged from 1 month to 45 years (on average 13,3±0,26 years). The study of patients with ADPV included electrocardiography and radiography on various days after surgery. The analysis of the features of the course of the immediate postoperative period, depending on the type of defect. The dynamics of anatomical and functional parameters of operated patients with abnormal pulmonary venous depression were studied. Changes in heart parameters after correction using electrocardiography and radiography were analyzed. The aim of the study was to study the ECG and X-ray cardiometric parameters of patients with abnormal pulmonary venous depression in the immediate postoperative period. Keywords: congenital heart disease, abnormal pulmonary vein drainage, pulmonary hypertension, electrocardiography, radiography, evaluation of results.
Keywords: Congenital heart disease, abnormal pulmonary venous drainage, pulmonary hypertension, electrocardiography, radiography, outcome assessment.